Distributed Simulation of Large-Scale Individual Oriented Models - Mostaccio, Diego (2006)
The distributed simulation for high performance models has been carried-out into a very useful and low-cost tool. In the present work their application to an individual oriented model (Fish Schools) is analyzed. To do this, it was analyzed different alternatives for this type of simulation and their application to obtain performance and model scalability using different implementation. Thus, two distributed simulator have been developed based on PVM and MPI communication libraries. This paper resumes the advantages and drawbacks of each implementation and some conclusions about the distributed simulation for this type of models are extracted. Moreover, visualization aspects and the developed infrastructure based on OpenGl are described.